Improvements of LHC data analysis techniques at Italian WLCG sites. Case-study of the transfer of this technology to other research areas. Issue 3 (December 2015) - Solestizi, L Alunni; Argiro, S; Bagnasco, S; Barberis, D; Barone, L M.; Boccali, T; Bonacorsi, D; Candelise, V; Carlino, G; Casula, E; Ciangottini, D; De Salvo, A; et al.
Abstract: In 2012, 14 Italian institutions participating in LHC Experiments won a grant from the Italian Ministry of Research (MIUR), with the aim of optimising analysis activities, and in general the Tier2/Tier3 infrastructure. We report on the activities being researched upon, on the considerable improvement in the ease of access to resources by physicists, also those with no specific computing interests. We focused on items like distributed storage federations, access to batch-like facilities, provisioning of user interfaces on demand and cloud systems. R&D on next-generation databases, distributed analysis interfaces, and new computing architectures was also carried on. The project, ending in the first months of 2016, will produce a white paper with recommendations on best practices for data-analysis support by computing centers.